Effect of Glass Fiber Reinforcement on the Mechanical Properties of Acrylic Resin Denture Base - Jane Amelia Vebriani Wibisono; Hernindya Dwifulqi; Calvin Kurnia; Axel Adryanto (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2025)
Background: Acrylic resin dentures are frequently reported to experience damage within a few years after fabrication. Intraorally, repeated masticatory forces can lead to fatigue failure and fracture, while high extraoral impact forces, such as accidental drops, may also lead to fractures of the denture base. Objective: To determine the optimal concentration of glass fibers reinforcement that provides the highest values of impact strength, transverse strength, and hardness in acrylic resin. Materials and Methods: A total of 48 acrylic resin samples were divided into four groups based on glass fiber concentration: 0%,6%,9%, and 12%. Each group was tested for impact strength, transverse strength, and hardness. Samples dimension for impact strength: 65 mm x 10 mm x 2.5 mm, 80 mm x 10 mm x 4 mm for transverse strength, and tube-shaped with a diameter of 5 mm and a thickness of 3 mm for hardness test. Testing equipment for impact strength: Charpy testing machine (Resil Impactor Ceast 6958.000), Universal Testing Machine (Shimadzu AGS-X 10kN for transverse strength, and Vickers machine (HMV-G) for hardness test. Results: The highest impact strength was observed in the group with 0% glass fibers. Meanwhile, the addition of 12% glass fibers exhibited the highest transverse strength exhibited and the highest hardness was achieved in samples containing 6% glass fibers. Conclusion: The addition of 12% glass fiber enhances the transverse strength of acrylic resin but decreases impact strength. Meanwhile, adding 6% glass fiber improves the hardness of acrylic resin.